Killing and Dying for Public Relations - Ryan, Cheyney (Conatus - Journal of Philosophy, 2023)
My starting point is the first major American military action in World War II in Europe, “Operation Torch.” The action was controversial because the American military regarded it as militarily useless, if not counterproductive. But the military was overruled by President Roosevelt on the grounds that, while it was not militarily necessary, it was politically justified. This indifference to military necessity seems to violate standard rules about the legitimacy of military force. The larger question it raises is the relation between military concerns and political ones in warfare. Much of this essay explores the relation between these two dimensions in war: the military dimension and the political dimension. I argue that the second dimension is the most important one, as well as the most problematic one for the legitimacy of war. Yet it is ignored by standard just war theories. I then return at the end to consider again the problems raised by “Operation Torch,” and especially the question of the harms inflicted on a country’s own soldiers – in the name of killing and dying for public relations.